Implementation of the SN04 Roko metal sensor on a 5.56 mm caliber portable magazine feeder - Fajar Dermawan Tamboenan; Mokhammad Syafaat; Ade Setiawan; Dekki Widiatmoko; Rafi Maulana Al-farizi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Roko SN04 Metal Sensor technology and equipment are evolving and growing more advanced with time. One type of equipment that needs to consider both the user's safety and the equipment's development and safety is technological equipment used in the military. The soldiers can shoot and do so with skill. As a result, soldiers must be able to move swiftly against the enemy and vigilant when utilizing combat equipment to ensure that it is used correctly and for its intended purpose. Nevertheless, there are still several fighting tools in the military that require a lot of physical labor, making them exceedingly inefficient for the user. One such tool is the portable magazine for 5.56-millimeter ammunition. This study employed the 4D methodology, which stands for Define, Design, Develop, and Disseminate. Development research is a part of this methodology. A device for loading magazines has been created to make it easier for soldiers to move in situations where loading bullets by hand is still risky and impractical. The Roko SN04 sensor is used in the construction of this tool. One sensor that can be used as a metal detector is the Roko SN04. This magazine refill gadget uses a DC motor as a mechanic and an Arduino as a control to randomly arrange ammunition. This study's success rate was 96.67%